Developing an improved risk-adjusted net present value technology valuation model for the biopharmaceutical industry - Jonghak Woo; Eungdo Kim; Tae-Eung Sung; Jongtaik Lee; Kwangsoo Shin; Jeonghee Lee (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
The financial valuation of a drug that is still under development is required for various purposes. The risk-adjusted net present value (r-NPV) method, which recently emerged in the biotech industry, uses the development attrition rate as a discount factor to reflect risk during each development phase. The r-NPV method was developed to overcome the disadvantages of the prevailing discounted cash flow and real options methods and considers drug type, as well as the stage of development in its approach. Using this method, the current study examines technology values in the biopharmaceutical industry and matches the clinical development periods and success rates of these new drugs by analyzing datasets from ClinicalTrials.gov and MedTrack DB. It thus provides support for an empirical valuation model for experts in the field. Notably, there is limited research on the attrition rate and development period of new substance drugs and the research results are not consistently presented. In addition to new substance drugs, further research is necessary to deepen understanding of the attrition rate and development period of biologically-based drugs because of their inherent physical and developmental differences. Similarly, research on performance specifics within drug class models would enable refinement of the model.
Keywords: 650; clinical trials development period; discounted cash flow; likelihood of approval; net present value; possibility of success; risk adjusted valuation